Pretherapeutic functional neuroimaging predicts tremor arrest after thalamotomy. (7th January 2018) - Tuleasca, C.; Najdenovska, E.; Régis, J.; Witjas, T.; Girard, N.; Champoudry, J.; Faouzi, M.; Thiran, J.‐P.; Bach Cuadra, M.; Levivier, M.; Van De Ville, D.
Abstract : Objective: Essential tremor (ET) represents the most common movement disorder. Drug‐resistant ET can benefit from standard stereotactic procedures (deep brain stimulation or radiofrequency thalamotomy) or alternatively minimally invasive high‐focused ultrasound or radiosurgery. All aim at same target, thalamic ventro‐intermediate nucleus (Vim). Methods: The study included a cohort of 17 consecutive patients, with ET, treated only with left unilateral stereotactic radiosurgical thalamotomy (SRS‐T) between September 2014 and August 2015. The mean time to tremor improvement was 3.32 months (SD 2.7, 0.5‐10). Neuroimaging data were collected at baseline (n = 17). Standard tremor scores, including activities of daily living (ADL) and tremor score on treated hand (TSTH), were completed pretherapeutically and 1 year later. We further correlate these scores with baseline inter‐connectivity in twenty major large‐scale brain networks. Results: We report as predictive three networks, with the interconnected statistically significant clusters: primary motor cortex interconnected with inferior olivary nucleus1, bilateral thalamus interconnected with motor cerebellum lobule V 2 (ADL), and anterior default‐mode network interconnected with Brodmann area 10 3 (TSTH). For all, more positive pretherapeutic interconnectivity correlated with higher drop in points on the respective scores. Age, disease duration, or time‐to‐response after SRS‐T were not statistically correlated with pretherapeutic brain connectivity measures ( P > .05). The same applied to pretherapeutic tremor scores, after using the same methodology described above. Conclusions: Our findings have clinical implications for predicting clinical response after SRS‐T. Here, using pretherapeutic magnetic resonance imaging and data processing without prior hypothesis, we show that pretherapeutic network(s) interconnectivity strength predicts tremor arrest in drug‐naïve ET, following stereotactic radiosurgical thalamotomy.